On the human perception of dissimilarities between postures of humanoids. (1st November 2016) - Basoeki, Fransiska; DallaLibera, Fabio; Ishiguro, Hiroshi
Graphical Abstract: Abstract : This paper analyzes the perceived dissimilarity between postures of humanoid robots. First, the human perception of absolute distance between postures is focused. It is shown that results derived in computer graphics for human figures can be replicated with humanoids, despite the difference in body proportions and arrangement of the degrees of freedom. Successively, the perception of relative distances between postures is considered. It is shown that, paradoxically, better prediction of the distance between a pair of postures does not necessary lead to better predictions of which of multiple distances is the shortest. Finally, the paper concludes by briefly discussing possible implications of this finding to the fields of motion retrieval and motion blending.